PENGARUH PROGRAM LOYALITAS DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi pada Starbucks Coffee Indonesia) - Nugraha, Raihan Ananta; Kusumawardhani, Amie (Diponegoro Journal of Management, 2024)
ABSTRACT Nowadays, loyalty programs are a marketing strategy that presents programs or incentives aimed at consumers who remain loyal. A carefully crafted loyalty program can improve brand image by providing customers with a positive experience and unique benefits, which ultimately increases customers' positive brand image of the brand. loyalty programs and brand image are used by companies to collect information and increase customer loyalty and customer satisfaction. This research seeks to explore the impact of loyalty programs and brand image on customer loyalty with customer satisfaction as a mediating variable. This research was designed using a questionnaire and measured using the Semantic Differential Scale. Data collection was carried out using a questionnaire method distributed using Google Form. The sample in this study consisted of 200 respondents with the criteria being 18-34 years old, who were Starbucks card users and had previously purchased products using a Starbucks card. The data obtained were analyzed using a quantitative and structural approach using the Structural Equation Modeling (SEM) method via AMOS version 26 software. The results of the research show that loyalty programs have no positive and significant influence on customer satisfaction, brand image has a positive significant influence on customer satisfaction, customer satisfaction has a positive significant influence on customer loyalty, loyalty programs have a positive and significant influence on customer loyalty, and brand image has a positive and significant influence on customer loyalty. In this research it was also found that customer satisfaction cannot significantly mediate the influence of program loyalitas on customer loyalty and customer satisfaction can mediate the influence of brand image on customer loyalty